Chronic hypothermia in multiple sclerosis. Issue 6 (June 1987) - Sullivan, F; Hutchinson, M; Bahandeka, S; Moore, R E
Abstract : Two patients with clinically definite multiple sclerosis presented with acute hypothermia and on recovery were found to be chronically hypothermic. Thermoregulatory studies indicated a central, hypothalamic defect which is presumed to be due to a plaque of demyelination.